Reduksi Sampah Rumah Tangga dengan Menerapkan Pengomposan Biopori dan Drum Komposter di Wilayah Jambangan - Mohamad Mirwan; Aulia Ulfah Farahdiba; Ryzki Marcella Amalia Triadi (Prosiding ESEC, 2022)
The problem of waste, especially household (organic) waste that has not been processed properly is certainly a big problem. The reason is because the waste management system and handling are not well organized. One solution in handling household waste (organic) can be done through composting using biopori infiltration holes and composter media. This study aims to determine the percentage of waste reduction, as well as to determine the comparison of compost yields from the two composting media. The study used 2 reactors in both composting media, with different initial waste weights. The composter uses variations in the initial weight of 3 kg and 4 kg of waste, while in the biopori using variations in the initial weight of waste 2 kg and 1 kg. The results of the percentage of waste reduction obtained from each reactor in the biopore are 50%, 25%, while in the composter are 63%, 50%. In the results of the percentage of waste reduction the best is found in the composting media with a composter. The compost quality parameters tested included pH, moisture content, C-organic, N-total, C/N ratio. The results show that the compost quality in the two composting media is closest to SNI 19-7030-2004 is composting media using a composter.